Adaptive collaborative management (ACM) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
ACM is a participatory approach that links forest stakeholders, empowers local communities and their subgroups, and strengthens adaptive capacities. It is a value-adding approach whereby people who have interests in a forest agree to act together to plan, observe and learn from the implementation of their plans while recognizing that plans often fail to achieve their stated objectives. ACM is characterized by conscious efforts among such groups to communicate, collaborate, negotiate, and seek out opportunities to learn collectively about the impacts of their actions.